“English teacher’s perceptions about task-based learning in efl teaching” - Fiallos Villegas, Rafael Higinio (2023)
Learning a new language is essential to break the barriers of communication in a globalized world. Hence, it is necessary for students to develop English language skills for effective communication, so, the implementation of task-based language teaching (TBLT) appears as an alternative to traditional teaching methods. However, the limited number of studies related to this topic in the Ecuadorian educational context makes it difficult to know the benefits and challenges of applying (TBLT). Thus, the main objective of this study is to determine an English teacher´s perceptions of Task-Based Learning in English as a Foreign Language (EFL) teaching in relation to the benefits and challenges in classroom implementation. A qualitative approach and a descriptive method were used to hold this study. A semi-structured interview guide with 20 open-ended questions was applied to collect data based on perceptions about the use of (TBLT). The participant was a female English teacher who was selected through a purposive sampling technique, and the collected data was analyzed following the thematic analysis procedure. The main results of the study show that the participant had positive and challenging perceptions toward the implementation of (TBLT). Her positive aspects refer to the use of significant tasks, which helped the development of reading comprehension, as well as communicative skills, and even cognitive skills. Nevertheless, she stressed that the lack of knowledge makes it difficult to correctly apply the (TBLT), hindering knowledge convey and classroom management. In conclusion, it is possible to implement (TBLT) to achieve academic success in EFL teaching and start using the post methods the EFL national curriculum suggests, but for successful implementation, teacher training is necessary.